COVID-19 AND ITS RELATION TO ANOSMIA, AGEUSIA AND OTHER NEUROLOGICAL MANIFESTATIONS - ASSIRI, ABDULLAH M.; ALQURASHI, AFNAN SALMAN R.; MOAZIN, OTHILLAH MAHER S.; ALSAADI, GHADI KHALID K.; ABDALI, YOUSEF ALI H.; DUNDUR, ALHASSAN AHMED M. AL; ALNUWAYSIR, ALI MOHAMMED S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Background: Coronavirus disease (COVID-19) is an infectious disease and highly contagious caused by a newly discovered coronavirus (SARS-CoV-2),was firstly reported in Wuhan. SARS-CoV-2belongs to the family Coronaviridae, which belongs to the order Nidovirales. It has be report that bats are the primary natural reservoir that houses a number of CoVs. Risk Factors include: Age, Gender, Diabetes, Hypertension, Cardiovascular Diseases, Malignancy. The Aim: of this study to review the impact this virus has on the nervous system. And to explore the neurological manifestations experienced by coronavirus disease (COVID-19) patients. Methods: The study was a review article. Data was collected during the period from 1– 29 September, 2021. PubMed and EBSCO Information Services were chosen as the search databases for the publications used within the study. Topics concerning the updates in types, management, and outcomes the neurological manifestations of Covid-19 cases, published in English around the world. No software was utilized to analyze the data. The data was extracted based on our specific objectives. Results: Myalgia, headache, altered sensorium, hyposmia, and hypogeusia were the most commonly reported neurological signs of COVID-19. COVID-19 can also cause ischemic stroke, intracerebral hemorrhage, encephalomyelitis, and acute myelitis in the central nervous system, as well as peripheral nervous system manifestations like Guillain-Barré syndrome and Bell's palsy and skeletal muscle manifestations like rhabdomyolysis in the peripheral nervous system. Conclusion: We conclude that neurological manifestations includingischemic strokes, hypogeusia, hyposmia represents the most evident neurological manifestations in COVID-19 patients.